TRAINING ON PREPARATION FINANCIAL STATEMENTS BASED ON SAK EMKM FOR MSMEs IN GENTENG DISTRICT SURABAYA: PELATIHAN PENYUSUNAN LAPORAN KEUANGAN BERBASIS SAK EMKM PADA UMKM KECAMATAN GENTENG SURABAYA - Setyabudi, Teguh Gunawan; Suwitho, Suwitho; Palupi, Dian; Iswara, Ulfah Setia (Faculty of Vocational Studies, Universitas Airlangga, 2025)
Background: Genteng District, located in the center of Surabaya, is home to many micro, small, and medium enterprises (MSMEs) that hold significant potential for community-based economic growth. However, many of these MSMEs lack formal financial reports, which are essential for evaluating business performance. To support their development, financial literacy-particularly in the preparation of financial statements-is critically needed. Objective: This community service initiative aimed to provide training on financial report preparation for MSMEs in Genteng District. Method: The program consisted of several stages: identifying the needs of the MSME partners, conducting socialization and training sessions, and carrying out monitoring and evaluation activities. The program involved 35 MSMEs operating in the culinary and handicraft sectors. Results: The training involved practical guidance, including examples of financial reports and transaction identification for each business. Participants learned how to post transactions into journals and ledgers, leading to the preparation of financial statements in accordance with Financial Accounting Standards (SAK). The training significantly enhanced participants' skills in preparing financial reports. Conclusion: MSMEs have become more aware of the importance of financial report preparation as a tool for evaluating business performance.